Designing a Model for the Development of Digital Competencies among Public Sector Employees: A Case Study of Governmental Organizations in Kermanshah - Rezaei, Farhad; Bastami, Masoud; Sheikh Esmaili, Saman (Future of Work and Digital Management Journal, 2024)
In the era of digital transformation, public sector organizations face significant challenges in updating the capabilities of their human capital. Digital competencies have emerged as one of the most critical components for the successful implementation of innovative policies and the effective utilization of emerging technologies. Purposeful development of employees’ digital competencies not only enhances productivity but also plays a pivotal role in organizational flexibility and sustainability. This study aims to design a conceptual model for the development of digital competencies in governmental organizations in the city of Kermanshah and seeks to identify and explain the dimensions, requirements, and barriers to this development. Employing a qualitative approach and thematic analysis method, data were collected through semi-structured interviews with 12 academic and executive experts in the fields of human resource management and information technology. For data analysis, the four-stage thematic analysis process based on the Clarke and Braun model was used, including initial coding, theme searching, reviewing, naming, and presenting the final model. The findings of the study led to the identification of four main themes: employee digital competencies, organizational enabling factors, barriers to competency development, and the role of external stakeholders. Furthermore, 13 sub-themes and more than 20 initial codes were identified to support the development of the conceptual model. According to the results, developing digital competencies in public sector organizations requires a systemic, interdisciplinary perspective grounded in continuous learning, leadership support, and inter-organizational collaboration. The final proposed model can serve as a practical guide for policymakers and human resource managers in designing and implementing digital transformation programs.